Pengelolaan Hutan Bersama Multistakeholder melalui Pengembangan Agroforestry Kopi Organik di Kawasan Hutan Darajat Kabupaten Garut - Okke Rosmala Dewi; Ibrahim Danuwikarsa, Maraden Panggabean (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
One of the causes of environmental disasters that have occurred lately is the conversion of forest areas that occur in upstream areas of the river flow. Like in the protected forest area of ​​Darajat, Garut Regency, the conversion of functions of the forest area into horticultural land is rapid and massive. This causes environmental damage, environmental pollution and prone to natural disasters such as landslides and forest fires. With the decreasing capacity of forest resources, a comprehensive, participatory and sustainable forest area management system is needed with a partnership approach, economic development, environmental sustainability and involving stakeholders. Multistakeholder Collaborative Forest Management through the development of Agroforestry Organic coffee is one alternative in reducing forest area conversion, enhancing environmental conservation and reducing the risk of natural disasters. The integrated and integrated program starts from an inventory of natural & forest resources, mapping the socio-economic conditions of forest village communities, joint planning of forest area management by involving the Forest Village Community Institute (LMDH) and stakeholders, implementing community-based environmental management awareness programs, implementing rehabilitation and conservation on critical land through commodity transfer location and transfer of profession. Technical and social assistance, Monitoring and evaluation together and periodically as well as securing forest areas together. All of that was done to restore the function of the forest area to sustainable forests and disaster preparedness.